Correlation of dendritic cell infiltration with active crypt inflammation in ulcerative colitis - Watanabe, Shinichiro (Clinical immunology (Orlando, Fla.), 2007)
The aim of this study was to evaluate the histological localization and phenotypic characteristics of infiltrating dendritic cells (DCs) and to examine the relationship between the degree of DC infiltration and the severity of inflammation in the colonic mucosa in ulcerative colitis (UC). Also explored was the expression of macrophage inflammatory protein-3alpha (MIP-3alpha), and its receptor CC-chemokine receptor 6 (CCR6), to evaluate the significance of immature DCs in the crypt inflammation evident in UC. There was a significant positive correlation between the number of infiltrating DCs and the degree of crypt inflammation, mononuclear cell infiltration, crypt atrophy, and comprehensive active inflammation. No significant correlation between the number of S-100 protein(+) cells and the severity of crypt atrophy was found. S-100 protein(+), MIP-3alpha(+), and CCR6(+) cells were frequently localized in or around the crypt with inflammation. MIP-3alpha(+) neutrophils and S-100 protein(+) CCR6(+) cells with dendritic morphology were detected in or around the crypt inflammation. Both S-100 protein(+) DCs and CCR6(+) cells were frequently clustered in the surface mucosa beneath the surface epithelium when the crypt was not inflamed. CD1a(+) Langerhans-cell-type DCs were not found in any of the tissues examined. These data indicate that DCs participate not only in chronic inflammation but also in active crypt inflammation